2022
DOI: 10.1039/d2tc02817d
|View full text |Cite
|
Sign up to set email alerts
|

Energy-saving chromium-activated garnet-structured phosphor-converted near-infrared light-emitting diodes

Abstract: Phosphor-converted near-infrared light-emitting diodes (pc-NIR LED) are smart and energy-saving light sources as compared with the conventional tungsten halogen light bulb that will enable upcoming modern devices to meet the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 62 publications
(85 reference statements)
0
19
0
Order By: Relevance
“…The choices of cations (A, B, and C) for garnet and their concurrent effect on the polyhedral features and their types are briefly discussed in our previous review paper. 7 One of the primary reasons for using garnet structures for Cr 4+ luminescence is their structural rigidity, which can provide higher quantum efficiency, thermal stability, and longer centered wavelengths. In addition, the garnet system offers a wider choice of chemical elements and can also be able to synthesize on a mass scale.…”
Section: Strategies To Accommodate Cr 4+ Ions In the Garnet Structurementioning
confidence: 99%
See 3 more Smart Citations
“…The choices of cations (A, B, and C) for garnet and their concurrent effect on the polyhedral features and their types are briefly discussed in our previous review paper. 7 One of the primary reasons for using garnet structures for Cr 4+ luminescence is their structural rigidity, which can provide higher quantum efficiency, thermal stability, and longer centered wavelengths. In addition, the garnet system offers a wider choice of chemical elements and can also be able to synthesize on a mass scale.…”
Section: Strategies To Accommodate Cr 4+ Ions In the Garnet Structurementioning
confidence: 99%
“…The significance and concept of this strategy are demonstrated in Cr 3+ -doped phosphors. 7 The substitution at the octahedral environment can directly regulate the crystal field strength around Ni 2+ ions. It is recognized that the crystal field strength is inversely proportional to the bond length of the localized octahedral environment.…”
Section: Crystal Field Strength Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadband near-infrared (NIR) light has drawn much attention in the application field of organic analysis. , Numerous studies have been reported on broadband NIR emission with high thermal stability and high quantum efficiency produced by transition-metal activators. In particular, Cr 3+ ion is the most preferred activator among these transition metals due to the good performance in these related aspects. For example, La 3 Ga 5 GeO 14 :Cr 3+ has a broadband NIR emission with a full width at half-maximum (FWHM) of 330 nm, and Gd 3 Sc 2 Ga 3 O 12 :Cr 3+ has a near-unity internal quantum efficiency . The codoping of Cr 3+ and some rare earth ions (Yb 3+ , Eu 2+ , and Ce 3+ ) could further improve the properties of the NIR phosphors .…”
mentioning
confidence: 99%